PERIPHERAL PUDDLING OF CONTRAST-CLASSICAL ENHANCEMENT PATTERN OF GIANT CAVERNOUS HEPATIC HEMANGIOMA REVEALED ON COMPUTED TOMOGRAPHY IN AN ADULT MALE: Giant Cavernous Hepatic Hemangioma - Amin, Muhammad Umar; Mahmood, Rabia; Shafique, Mobeen (Pakistan Armed Forces Medical Journal, 2008)
.